Pengaruh Return On Asset dan Net Profit Margin Terhadap Harga Saham - Abdul Hamid; Dailibas Dailibas (COSTING : Journal of Economic, Business and Accounting, 2021)
In the last few years, the national automotive industry has shown fairly attractive developments that are in great demand. This study aims to examine the effect of ROA and NPM on stock prices in automotive and component manufacturing companies listed on the IDX for the 2014-2019 period. The sample in this study there were 5 companies from 13 companies as a population, sampling using purposive sampling, so that the number of samples studied was 30 data for 6 years. The research method used is descriptive quantitative research methods. Based on the results of the research conducted, the authors concluded with the t test and f test, namely: ROA has a negative effect on stock prices, NPM has a positive effect on stock prices. Simultaneously ROA and NPM have an effect on stock prices. Based on this research, it is known that the stock price can be described as 53.3% by ROA and NPM and there are still 46.7% other factors outside the independent variables in this study that can describe the stock price. Keywords: ROA, NPM, Stock Price.